An Introductory Set of Activities Designed to Facilitate Successful Combinatorial Enumeration for Undergraduate Students. Issue 10 (25th November 2016) - Lockwood, Elise; Swinyard, Craig A.
Abstract: In this paper, we present a set of activities for an introduction to solving counting problems. These activities emerged from a teaching experiment with two university students, during which they reinvented four basic counting formulas. Here we present a three-phase set of activities: orienting counting activities; reinvention counting activities; and outcome-focused review activities. In presenting the activities, we include a list of sample tasks, suggestions for prompts for effective implementation, and data excerpts that provide evidence for the effectiveness of these activities.